ANALISIS MANAJEMEN MODAL KERJA PADA INDUSTRI DASAR DAN KIMIA - Farah Margaretha; Ayu Puspita (Media Riset Bisnis & Manajemen, 2007)
The objective of this research is to observe the working capital management on basic industry and chemical companies. Data research were obtained from 21 basic industry and chemical companies which are listed on the Jakarta Stock Exchange and this research was using the descriptive method, in order to observe the working capital management effectiveness by using the net working capital to sales ratio, current ratio, quick ratio, inventory turnover, account receivables turnover and working capital turnover on the basic industry and chemicai companies and also using the hypothesis testing method in order to observe whether the working capital management was measured by using the cash conversion cycle.have an influence towards the profitability. Data analysis method was using the working capital analysis, cash conversion cash analysis, profitability analysis (operating profit margin), classic assumption test, fit model test, hypothesis test (t-test). Based on the statistic test, obtained that the working capital management have a negative influence towards the profitability. In order to achieve an effective and proper operational in the company, thus the basic industry and chemical companies should lessen the cash conversion cycle by: lessen the inventory conversion period, by selling the inventory in the warehouse earlier than predicted. Such as cement, ceramic, glass, sand, etc; lessen the receivable collection period by collecting the account receivables; the payables deferral period will be extended by delaying the payment. A short cash conversion cycle could provide a better profit, because the longer the cash conversion cycle, the external fund and other funds requirement will also perceived higher.Keywords : working capital management, financial ratio